Blended game-based learning environments: Extending a serious game into a learning content management system - Dunwell, Ian; Petridis, Panagiotis; Arnab, Sylvester; Protopsaltis, Aristidis; Hendrix, Maurice; De Freitas, Sara (Proceedings - 3rd IEEE International Conference on Intelligent Networking and Collaborative Systems, INCoS 2011, 2011)
Serious games have recognized potential as a means to tackle many challenges in education, ranging from stimulating increased learner motivation, to transferring challenging concepts in a novel and engaging form. They are commonly shown to work most effectively in blended approaches to learning, whereby the game plays a core role in a wider pedagogic approach, often based around an experiential or exploratory model. In this paper, we explore how the integration of a serious game, and more generally gaming paradigms, can be extended to a learning content management system (LCMS) to support a blended and holistic approach to their use in education. Through a case study within the EU-Funded Adaptive Learning via Intuitive/Interactive, Collaborative and Emotional Systems (ALICE) project, we demonstrate a technical integration of a gaming engine with a proprietary LCMS, and discuss the broader pedagogic benefits of such an approach. In particular, we note how this method can support an 'intuitive guided' or scaffolded approach to learning, where the learner is given the potential to explore a non-linear learning environment, whilst scaffolding and blending provides the guidance towards ensuring targeted learning objectives are met. © 2011 IEEE.
Created from Fastlane, Scopus look-up
Keywords: Blended learning; Game-based learning; Learning content management systems; Pedagogy; Serious games; Technology enhanced learning